2011
DOI: 10.1017/s0007114511005046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two commercially available feline diets on glucose and insulin concentrations, insulin sensitivity and energetic efficiency of weight gain

Abstract: A low-carbohydrate, high-protein (LCHP) diet is often recommended for the prevention and management of diabetes in cats; however, the effect of macronutrient composition on insulin sensitivity and energetic efficiency for weight gain is not known. The present study compared the effect in adult cats (n 32) of feeding a LCHP (23 and 47 % metabolisable energy (ME)) and a high-carbohydrate, low-protein (HCLP) diet (51 and 21 % ME) on fasting and postprandial glucose and insulin concentrations, and on insulin sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 42 publications
7
78
1
Order By: Relevance
“…There is also a relationship with treat feeding and obesity and it has been observed that overweight cats tend to be fed more treats than normal weight cats (Russell et al 2000;Kienzle and Bergler 2006). Dietary fat and energy density are positively associated with weight gain in ad libitumfed cats, while carbohydrate content above 40% of metabolisable energy (ME) is negatively associated with weight gain Coradini et al 2011;Hewson-Hughes et al 2011). There appears to be a "carbohydrate ceiling" in cats whereby, at carbohydrate levels found in many economy feline diets (> 40% ME), energy intake is reduced to limit carbohydrate intake Hewson-Hughes et al 2011).…”
Section: Dietary Factorsmentioning
confidence: 99%
“…There is also a relationship with treat feeding and obesity and it has been observed that overweight cats tend to be fed more treats than normal weight cats (Russell et al 2000;Kienzle and Bergler 2006). Dietary fat and energy density are positively associated with weight gain in ad libitumfed cats, while carbohydrate content above 40% of metabolisable energy (ME) is negatively associated with weight gain Coradini et al 2011;Hewson-Hughes et al 2011). There appears to be a "carbohydrate ceiling" in cats whereby, at carbohydrate levels found in many economy feline diets (> 40% ME), energy intake is reduced to limit carbohydrate intake Hewson-Hughes et al 2011).…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Given that postprandial serum glucose and insulin concentrations in obese cats can be drastically changed and altered by diet, as compared with healthy cats [8,26], we assessed and compared the influence of four different commercially available prescription feline diets on in terms of postprandial glucose, insulin, triglyceride (TG) and nonesterified fatty acid (NEFA) concentrations, four important key parameters often monitored and assessed in obese and diabetic cats. There are currently a large number of diets available commercially for cats, which vary greatly in nutrient composition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theories suggest that high-carbohydrate diets may lead to DM in felines, since carnivores are not well adapted to readily metabolize large amounts of glucose efficiently, as a source of energy [20]. Moreover, cats lack salivary amylase and demonstrate low activity of intestinal enzymes commonly involved in carbohydrate breakdown, such as intestinal amylase and disaccharidases [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations